'Asking the hard questions': Improving midwifery students' confidence with domestic violence screening in pregnancy. (January 2018) - Smith, Rachel; Wight, Raechel; Homer, Caroline S.E.
Abstract: Domestic violence is a global public health issue. Midwives are ideally placed to screen for, and respond to, disclosure of domestic violence. Qualified midwives and midwifery students report a lack of preparedness and low levels of confidence in working with women who disclose domestic violence. This paper reports the findings from an education intervention designed to increase midwifery students' confidence in working with pregnant women who disclose domestic violence. An authentic practice video and associated interactive workshop was developed to bring the 'woman' into the classroom and to provide role-modelling of exemplary midwifery practice in screening for and responding to disclosure of domestic violence. The findings demonstrated that students' confidence increased in a number of target areas, such as responding appropriately to disclosure and assisting women with access to support. Students' confidence increased in areas where responses needed to be individualised as opposed to being able to be scripted. Students appreciated visual demonstration (video of authentic practice) and having the opportunity to practise responding to disclosures through experiential learning. Given the general lack of confidence reported by both midwives and students of midwifery in this area of practice, this strategy may be useful in supporting midwives, students and other health professionals in increasing confidence in working with women who are experiencing domestic violence. Highlights: Domestic violence is a major global public health issue. Midwives are ideally placed to screen pregnant women for domestic violence. Responding to a disclosure of domestic violence is highly emotional work. Midwives and midwifery students lack confidence in responding to disclosure of violence. Experiential learning activities of authentic practice and supported practise increases student confidence.